Aligning the Outputs of the Department of Phydical Education and Sports Science with the Needs of Omani Labor Market in Light of Oman Vision 2040 - Abdullah Al Qaidi; Majid Al Busafi; Qusai Al-Kalbani; Al Mutaz Al Maamari; Tariq Al Jahwari; Hilal Al Hadabi; Nusaiba Ambo-Ali; Khalsa Al-Habsi; Arwa Al-Harrasi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
This study aims to align the outputs of the Department of Physical Education (PE) and Sports Science at Sultan Qaboos University, Oman with the needs of the Omani labor market for specialists in sports management in light of Oman vision 2040. The study used a descriptive approach using a questionnaire, and the size of the research sample was 211 respondents from institutions related to the field of physical education and sports science, and who are benefiting from the outcomes of sports management. The results of the study reveal that there is an urgent need to introduce a sports management major in the Department of Physical Education and Sports Science at Sultan Qaboos University. The researchers recommend that the Department of PE and Sports Science should be informed about the experiences of similar departments at other higher education institutions that have introduced such programs. Furthermore, it is necessary to form of a joint committee between the department and the concerned institutions to discuss the needs of the labor market, to review the department's policies towards introducing the specialty of sports management, and to consider the possibility of adapting the study plan for partnership with colleges related to sports management to offer majors serving students specializing in sports management..